Análisis de sistema CRM como soporte para la gestión de ventas para el negocio “De Todo Para Tu Celular” - Jiménez Muñoz, Bélgica (2021)
Customer service constitutes the basic contact experience between the organization and the customer. The correct way to carry out this relationship depends on the customer's retention or loss. Therefore, organizations must treat customer service as the basic element of the meaning of their existence and relevance. Customer service in the organization seeks essentially to satisfy those needs presented by the customer, which is why it can be said that the absence of demand for services does not allow organizations to develop projects that revolve around it. Faced with the service as an essential factor in the organization, several tools have been developed in order to have a continuous improvement in meeting the needs of customers, one of them is the CRM (Customer Relationship Management) that in this article is presented as an important tool to generate impact on customer services for the business "De todo para Tu Celular".